A case study of factors influencing primary healthcare Continuity of Care for persons with disabilities - Padayachee, Thesandree (Department of Health and Rehabilitation Sciences, 2025)
Background: “Continuity of Care” refers to how a patient experiences care over time and is considered to be a central pillar in the delivery of high-quality person-centred healthcare. In South Africa (SA), persons with disabilities experience a range of structural barriers to health services and even when access to health services is realised, poorly integrated health systems and services, limited human resources and poor awareness of the needs of persons with disabilities result in unmet healthcare needs. Given the rapidly transforming healthcare context of SA and the adoption of policies towards the realisation of universal health coverage, an understanding of how the health system is responding to the “Continuity of Care” needs of persons with disabilities through policy and practice is valuable step towards realising the goal of integrated people-centred health systems; particularly in the delivery of primary healthcare (PHC). Objectives: The study aimed to explore factors influencing “Continuity of Care” for persons with disabilities within the PHC context. Experiences and expectations of persons with disabilities were explored, relevant policies governing PHC and “Continuity of Care” were analysed and health systems responsiveness was explored to understand what influences “Continuity of Care” for persons with disabilities. Method: This exploratory case study used a critical social theory and a health policy and systems approach to better understand how primary healthcare “Continuity of Care” for persons with disabilities can be strengthened. The Conceptual Framework for Health Systems Responsiveness (Mirzoev & Kane, 2017) informed the case study design by exploring how persons with disabilities experienced “Continuity of Care” and supported a deeper understanding of health systems gaps through perspectives of service providers in responding to the “Continuity of Care” needs of persons with disabilities. The study was conducted within the context of the SA primary healthcare policy and implementation in an urban suburb in the city of Durban, KwaZulu Natal in South Africa. The study included multiple data collection methods including interviews, focus group discussions, document reviews and analysis of relevant policies using an adapted EquiFrame (Amin, 2011). Qualitative data was analysed thematically using inductive and deductive analysis. Results: Participants with disabilities were found to experience primary healthcare discontinuity resulting from known factors such as lack of reliable and accessible transport, negative attitudes of health facility staff and sub-optimal management of clinic and outreach services. New insights that were found to negatively affect “Continuity of Care” for persons with disabilities included the combined influences of institutional distrust; the medical model as a legacy of apartheid; incoherence in policies supporting “Continuity of care” and poor user-centred design practices in the delivery of new innovations that were unresponsive to the needs of persons with disabilities. Positive influences on “Continuity of Care” included emergent community leadership, family resilience to navigate through treatment uncertainty and supportive servant leadership styles of healthcare providers. Conclusion: The study points to the need for an expanded understanding of “Continuity of Care” for persons with disabilities within an African paradigm where care continuity extends beyond the health facility and with a stronger emphasis on community driven models of care that respect the role and influence of traditional health practitioners and cultural practices. More research is needed to better understand institutional distrust and how traditional western models of healthcare can be reshaped to deliver services.